(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this article, in a brief review of the literature, the data obtained on the evaluation of the effectiveness of the use of the Eyxhorniya algae supplement ispresented together with information about cases of stunted growth and reduced productivity, which is used as additional nutrients to bring the amount of protein substances lacking in the animal ration to the norm and to remove consumed heavy metals from the body as a result of the negative effects of heavy metal salts in different doses on the organism of agricultural-animals. According to the obtained data, decrement such as the growth and development of the experimental rabbits slowed down, productivity decreased, along with the amount of form elements in the blood and the amount of total protein in the blood serum and its fractions decreased from the normal level due to the negative effect of traditional farm ration, various amounts of cadmium and lead acetate added to it on the metabolic processes in the rabbits’ body. At the same time, the data obtained showed that the moderated metabolic processes in the body of rabbits of group 5 fed with the ration made of Eyxorniya were moderated and concluded accordingly.